Boganmeldelser - Henrik Tham; Ib Scheel Thomsen; Jytte Willadsen; Peter Gottlieb; Henrik Garlik Jensen; Britta Kyvsgaard; Madeleine Löfmarck; Peter Garde; Vagn Greve (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews